AN INTEGRATED APPROACH IN DESIGN, INSTALLATION AND COMMISSIONING OF MIRROR RTH AND GLOBAL INFORMATION SYSTEM CENTER (GISC) AT, PUNE - J K S, YADAV (MAUSAM, 2020)
WMO Information System (WIS)/Global Information System Center (GISC) and Mirror of Regional Telecommunication Hub (RTH) is basically a metadata catalogue web service and allows Data communication, synchronization of metadata with other Data Collection or Production Center (DCPC), GISCs or National Centers (NC’s) based on protocol OAI-PMH. Such catalogue is quite useful for rapidly integrating real-time and non- real- time data sets for better interpretation of weather systems by the forecaster (Singh et al., 2017).